The journey through time - Stilton, Geronimo (New York, NY : Scholastic Inc., 2014)
From the Jurassic period and the dinosaurs, to a medieval castle, Geronimo Stilton and a few members of his family embark on an adventure through time in Professor von Volt's new time machine, the Mouse Mover 3000.
Translation of: Viaggio nel tempo.
"Based on an original idea by Elisabetta Dami"--Colophon.
4.6.
3-6.
660L
Keywords: Stilton, Geronimo -- Juvenile fiction; Stilton, Geronimo -- Fiction; Mice -- Juvenile fiction; Time travel -- Juvenile fiction; Dinosaurs -- Juvenile fiction; Mice -- Fiction; Time travel -- Fiction; Dinosaurs -- Fiction; Adventure and adventurers -- Fiction; Adventure fiction; Adventure fiction